Decay of the Snow Cover Over Arctic Sea Ice From ICESat‐2 Acquisitions During Summer Melt in 2019. Issue 12 (23rd June 2020) - Kwok, R.; Cunningham, G. F.; Kacimi, S.; Webster, M. A.; Kurtz, N. T.; Petty, A. A.
Abstract: From the onset of melt in early June, corresponding declines in Ice, Cloud, and Land Elevation Satellite‐2 (ICESat‐2) freeboard and surface albedo can be seen over the entire Arctic sea ice cover. In the 2019 summer, area‐averaged freeboard decreased from 34 cm prior to melt to a minimum of 12 cm in August while the area‐averaged albedo decreased from ~0.7 to 0.38 for the same period. Calculations using ICESat‐2 freeboards and modeled ice thickness from Pan‐Arctic Ice Ocean Modeling and Assimilation System (PIOMAS) give area‐averaged snow depths ranging from 17 cm prior to melt to 3 cm in August over seasonal ice and from 34 to 4 cm over multiyear ice. Mean rates of snow ablation (including evaporation) in mid‐June were as high as 2 cm/day, comparable to field records from other years. Increases in freeboard after mid‐August in the high latitude (>80°N) multiyear ice cover, north of the Greenland coast, are likely due to earlier freeze‐up and snow accumulation in these regions with shorter melt seasons. Plain Language Summary: As the air temperature warms with the onset of summer, the Arctic Ocean ice cover undergoes its annual transformation from a highly reflective snow‐covered surface in winter to a darker, more absorbent surface during summer composed of bare ice, melt ponds, and open water. Several weeks after the onset of melt, much of the snow layer disappears as the snow is converted into meltwater. Over the entire ice cover, this loss of the snow layer can be seen in the lowering of surface heights measured by the lidar on NASA's Ice, Cloud, and Land Elevation Satellite‐2 (ICESat‐2). In this paper, we describe the changes in surface height and the corresponding changes in snow depth from the satellite observations and compare them with existing measurements from field programs, which are limited due to challenging logistics during the summer. We show, for the first time, that we can observe corresponding changes in surface height and reflectivity as well as the different rates of melt in the decay of the snow cover. These results will allow for an improved understanding of the impact of the snow layer on the fate of the ice cover at the end of the summer. Key Points: We provide a first look at the evolution of the summer ice cover in ICESat‐2 sea ice products Observations show a clear lowering of the freeboard associated with snow melt over the entire Arctic Ocean ice cover Area‐averaged snow depths ranged from 17 cm prior to melt to 3 cm in August over seasonal ice and from 34 to 4 cm over multiyear ice